ナンキョク イキ ニ オケル 1960-1975 ネンカン ノ チキュウ ジバ エイネン ヘンカ - 永田, 武; ナガタ, タケシ; Nagata, Takesi (1982)
P(論文) 南緯30°以南に在る地磁気観測所20点における地球磁場3成分(X, Y, Z) の1960年から1975年に至る15年間の永年変化を解析する。1960～1965,1965～1970,および19701975の3期間を通してZ>150nT/年に達する大きな永年変化が緯度70°～85°S, 経度20°W～60°Eの範囲に拡っている(図1a, b, c)。この南極域における大きなZの分布は地球磁場双極子能率の減少の影響と同双極子の北方移動の影響の重なりの結果に基づく部分が過半を占めている。北極域においては上記2現象の影響が互いに打ち消し合うので異常に大きな地球磁場永年変化は見られない。全地球面観測結果から求められた地球磁場双極子の2現象に基づく永年変化成分を観測値から差引いて求められた残余地球磁場永年変化(ΔX, ΔY, ΔZ)は, 南極域においてはまだ大きく, 経度20°W～50°E域にZ>50nT/年の正異常, 70°E～180°E域にZ≲-50nT/年の負異常という規則的な分布を示す(図4a, b, c)。地球の中, 低緯度帯においては残余地球磁場変化の過半部分が, 非双極子地球磁場の西方移動に因る事実が知られているが, 南極域においては, 非双極子地球磁場西方移動の影響は検知できない。その代わり, 非双極子地球磁場が0.3%/年の割合で増大しつつあると考えると南極域残余地球磁場永年変化の約80%を解釈することができる。 The annual mean values of the geomagnetic three components (X, Y, Z) at 20 stations located between the South Pole and the 30°S latitude circle during 15 years from 1960 to 1975 are examined to study on the geomagnetic secular variation in the southern polar region. In each of three periods, 1960-1965,1965-1970 and 1970-1975,the maximum positive annual rate, Z, over 150 nT/year, was located in a polar area of 70°-85°S in latitude and 20°W-60°E in longitude, as shown in Figs. 1(a), (b) and (c). The major parts of the geomagnetic secular variation in the Antarctic region can be attributed to a decrease of the centered geomagnetic dipole intensity and the northward shift of the geomagnetic dipole, both effects resulting in a decrease of the total geomagnetic force (F) and an apparent increase of Z (Z>0). In the north polar region, the two effects tend to cancel each other, but they are added to each other in the southern polar region. The two effects estimated from Yukutake-Cain's global analysis of the geomagnetic field (1979) are subtracted from the observed values of (X, Y, Z) at the Antarctic region stations. The residuals still show a considerably systematic regional secular variation pattern which can be represented by a positive anomaly of Z (Z>50nT/year) between 20°W and 50°E in longitude and a negative anomaly (Z≲-50nT/year) between 70°E and 180°E in longitude in the southern ...